Pengaruh Akuntabilitas, Partisipasi Masyarakat Dan Kompetensi Aparatur Desa Terhadap Pembangunan Desa - Subakti, Iwan Habib; Zanaria, Yulita; Hendri, Nedi (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze Accountability, Community Participation and Competence of Village Apparatuses for Village Development. This type of research is quantitative, in this study researchers used primary data through questionnaires with a population of 1053 families. The sampling technique used Slovin with several criteria so that 91 respondents were obtained. Data analysis in this study used the multiple linear regression analysis test method. The results of this study indicate that Accountability influences Village Development, Community Participation influences Village Development, Village Apparatus Competence influencesVillage Development.